Renin angiotensin system and pulmonary hemodynamics in chronic obstructive pulmonary disease - Chauhan, Preeti; Chetiwal, Rajesh (International Journal of Advances in Medicine, 2018)
Background: Pulmonary hypertension in chronic obstructive pulmonary disease (COPD) due to chronic alveolar hypoxia is probably the main contributor to the pathogenesis of pulmonary hypertension in COPD. Angiotensin II is a potent vasoconstrictor in renin angiotensin aldosterone system (RAAS), it has been shown to promote growth response in vascular smooth muscle cell contributing towards pulmonary hypertension. So, the Echocardiographicaliy measured MPAP and its correlation with RAAS in patients of COPD was evaluated. Methods: A prospective observational study was done in 32 patients with COPD and 10 age matched healthy, non-smoker subject included as controls. Stable patients requiring no change in their medication in the previous four weeks and not having had an acute exacerbation in that period were included. MPAP was calculated. Measurement of Ang II and aldosterone was done. Results: Thirty-two cases of COPD, meeting inclusion criteria were enrolled comprising of 32 males and the mean age of patients ±2sd was (55.6 ±16.8), while mean age of controls ± 2sd was 49.60 ±5.56. Arterial blood gas analysis, PaO2 was ranged from (mean±2sd 75.44±12.1), PaCo2 ranged from (mean ±2sd 41.36±3.79) and SpO2 ranged from (mean±2sd 94.03 2±.74). Mean ±2sd of plasma Ang II in COPD cases was (4.9±3.8) ng/dl, significantly higher in comparison with controls (p < 0.001). Mean ±2sd of plasma ACE activity was (51.12±26.9) in COPD. Mean ±2sd of plasma aldosterone was (182.35±364.2) in COPD cases with significant (p<0.01). The MPAP in COPD cases was (mean±2sd 34.53±7.70). Conclusions: Use of Doppler has the advantage of being noninvasive and has been shown to be extremely reproducible in evaluation of MPAP and CO. The increased level of Ang II with increase MPAP in the present study would suggest that this may be a suitable model for investigating effects of novel vasodilator drugs for the treatment of pulmonary hypertension developed due to COPD.